Pengaruh Kepemilikan Institusional, Umur Perusahaan, dan Struktur Modal Terhadap Nilai Perusahaan - Galuh Tresna Murti; Rr. Sri Saraswati; Faizi, Muhammad Fadly Nur (Owner : Riset dan Jurnal Akuntansi, 2024)
Firm value is an investor’s view of the level of success of a company associated with stock prices. The high value of a company will show shareholder prosperity and increase market confidence. The good value of the company will increase the interest of investors to invest in the company. The objective of this study is to determine the effect of institutional ownership, company age, and capital structure on firm value. In this study, 13 companies were involved as the study population with a unit sample of 65 healthcare sector companies listed on the Indonesia Stock Exchange. during the period 2018 to 2022 as research subjects. The sample selection technique in this study was purposive sampling. The data analysis method used in this study is descriptive statistics and panel data regression analysis using eviews 12.0 software. Descriptive statistics, classic firm assumption testing and hypothesis testing using the regression model for the information panels were used. Based on the results of the study, it is shown that institutional ownership, company age, and capital structure simultaneously have a significant effect on firm value. In the partial test of capital structure does not has a effect on the firm value, while the institutional ownership and company age have a effect on the firm value.